LAS BOÑIGAS DE VACA, EL ENCESPEDADO DE POA BULBOSA, Y LA DIVERSIDAD EN UN PASTIZAL DE DEHESA - Malo, J E Juan E; Suarez, F; Vaca, L A S Boñigas D E; Poa, E L Encespedado D E; Diversidad, Y L A; Un, E N; Dehesa, Pastizal D E (Pastos, 1996)
The interactions of cattle dung pats, the Poa bulbosa Turf and the number of species in a pasture is analyzed at a 10x10 cm scale, through a four-year monitoring of 50 dung pats. Dung pats elimínate the Poa bulbosa Turf, and its recovering takes more than four years. The rest of the species are also displaced by dung pats, but they colonize the gaps much faster. Thus, the number of species by sample is significantly smaller on dung pats the first year after deposition (5-4 vs. 10-8), not distinguishable the second and third years (9-2 vs. 10-0 and 9-3 vs. 8-0), and significantly higher the fourth year after depo- sition (13-8 vs. 10-7). These results seem to be associated to the competitive behaviour of Poa bulbosa. This species colonizes the gaps slowly, but it is able to displace other species from them. The effect of the process is relatively small for the whole pasture due to the small área covered by dung pats. However, due to the uneveness of dung deposi- tion it can contribute to the development of pasture gradients of composition and diver- sity associated to grazing.
Keywords: Central Spain; centro de españa; competencia; competition; dinámica de pastizales; disturbance; dung; excrementos; herbivores; herbívoros; pasture dynamics; perturbación